John Stuart Mill: market socialist?. Issue 3 (3rd July 2021) - McCabe, Helen
ABSTRACT: Compared to other elements of his political and economic thought, John Stuart Mill's claim to be 'under the general designation of Socialist' has largely been ignored. Where it has been acknowledged, it has generally been denied. One exception to this rule has been to link Mill with 'market socialism', primarily because of his commitments to worker-cooperatives and competition. These are both elements of Mill's socialism, but when we examine his position on production, distribution and exchange more carefully, it becomes much less clear that Mill endorses anything like a 'market' in his socialism. This paper offers a critical assessment of Mill's status as 'market socialist', considering, in particular, the 'ethos' he proposed for socialist organization of production and exchange, which is at odds with a profit-seeking motivation.